The Application of Article 7 Verses (2) Instructions of President Number 1 Year 1991 on the Distribution of Compilation of Islamic Law for Marriage Validation in Sleman Religious Courts - Sumardiyono Sumardiyono (Green Publisher Indonesia, 2025)
Not all couples married for years in Sleman Regency possess a marriage certificate, as stated in Article 7 Paragraph 1 of the Compilation of Islamic Law (KHI). Various factors contribute to this, including lost certificates due to disasters, carelessness, or marriages conducted solely under religious law (nikah siri). Couples who have lost their marriage certificate can request a duplicate from the KUA where they were married, providing a cover letter from their village and a loss certificate from the police. For those whose marriages are unregistered, applying for itsbat nikah at the Sleman Religious Court is advised. This study aims to describe the process of granting itsbat nikah and address the challenges faced in the Sleman Religious Court. Employing a descriptive research design with a qualitative approach, data was collected through document analysis related to itsbat nikah and interviews with Sleman judges. The findings indicate that the application of Article 7 Paragraph (2) KHI in Sleman should align with the 2014 guidelines from the Supreme Court of Indonesia’s Directorate General of Religious Justice. The legal outcome of establishing itsbat nikah at PA Sleman ensures the validity of marriages without certificates under State Administrative Law.